Новый клад комаровской культуры на Киевщине - Лысенко, С.С.; Лысенко, С.Д. (Материалы по археологии Северного Причерноморья, 2015)
In 2012 by the participants of search group «Korchaginec» (Boyarka city) the hoard of bronze items of Late Bronze Age was found. Hoard was transmitted on permanent storage in the funds of the Boyarka state regional museum. In the compound of were 9 bronze items: 2 bracelets, 2 double-stranded pendants with a hook, 2 spiral pendants of the Lubna type, 3 platen knife-razors. All things were fold in the certain order in a tulip vessel. Hoard can be attributed to the Komarov culture of Tshinets cultural circle and is dated by 13 century BC. The place of hoard's finding was examined and trenched by the Fastov archaeological expedition. The character of cultural layer and stratigraphy of monument are characteristic for the settlements, that allow us to interpret bronze items in a vessel exactly as treasure, but not as destroyed burial.